Public opinion on a mandatory COVID-19 vaccination policy in France: a cross-sectional survey. (March 2022) - Gagneux-Brunon, Amandine; Botelho-Nevers, Elisabeth; Bonneton, Marion; Peretti-Watel, Patrick; Verger, Pierre; Launay, Odile; Ward, Jeremy K.
Abstract: Objectives: Reaching the last pockets of unvaccinated people is challenging, and has led to the consideration of mandatory vaccination for coronavirus disease 2019 (COVID-19). Our aim was to assess attitudes toward mandatory COVID-19 vaccination in France before the announcement of—and factors associated with opposition to—this type of policy. Methods: Between the 10th and 23rd May 2021, we conducted a cross-sectional online survey among a representative sample of the French population aged 18 and over, and a specific sample of the French senior population aged over 65. Results: Among 3056 respondents, 1314 (43.0%) were in favour of mandatory COVID-19 vaccination, 1281 (41.9%) were opposed to such a policy, and 461 (15.1%) were undecided. Among opponents to mandatory COVID-19 vaccination for the general population, 385 (30.05%) were in favour of mandatory COVID-19 vaccination for healthcare workers (HCWs). In multivariate analysis, the age groups 18–24 and 25–34 years were significantly more opposed than the reference group (>75 years old) with respective adjusted odds ratio (aOR) and 95% confidence interval (95%CI) 4.67 (1.73–12.61) and 3.74 (1.57–8.93). Having no intention of getting COVID-19 vaccination was strongly associated with opposition to mandatory vaccination (aOR 10.67, 95%CI 6.41–17.76). In comparison with partisans of the centre, partisans of the far left and green parties were more likely to be opposed to mandatory COVID-19 vaccine, with respective aORs (95%CI) of 1.89 (1.06–3.38) and 2.08 (1.14–3.81). Conclusion: Attitudes toward mandatory COVID-19 vaccination are split in the French general population, and the debate might become politicized.